Climate Change Policy: The Effect of Real Options Valuation on the Optimal Mitigation-Adaptation Balance - Maybee, Bryan; Packey, Daniel; Ripple, Ronald (Economic Society of Australia, 2012)
This paper illustrates the static optimisation strategies for climate change mitigation and adaptation using net marginal benefit analysis, and goes on to develop a dynamic optimisation solution using a modified Hotelling approach. Unfortunately, the situation required for a Hotelling-type optimisation to hold is rarely observed in practice, as there are numerous sources of uncertainty that impact upon a forward-looking optimisation exercise. The situation is no different within the climate change debate, with opportunities and threats to the value-maximising exercise arising as uncertainties are resolved through new information. Choices of how to deal with and take advantage of these opportunities and threats are keys to identifying the optimal trade-off between the strategies, and need to be included in the calculation of the optimal mixture of mitigation and adaptation activities. Based on reasonable assumptions, this paper discusses the impact of the real options valuation technique on the theoreticalHotelling-type optimisation to show what the effects of its application would have on the theoretical dynamic optimal solution and what those economic implications represent to public policy.